Performance Evaluation of an Ironmaking System with Environmental Costs - Huimin Liu; Qiqiang Li (Complexity)
This paper proposes an exergoeconomic analysis method that considers environmental costs to make up for the lack of description of environmental costs in the traditional matrix model exergoeconomic analysis method. This method tracks the formation process of the product cost through life cycle and makes a useful exploration for revealing the true cost of the system product. According to actual needs, the principles for the construction of environmental emissions of products are proposed, and a detailed exergoeconomic analysis model is established by taking the iron smelting system as an example. Through calculation and analysis, the formation process and change rule of unit exergoeconomic cost of products in the system are revealed. Especially, considering the exergoeconomic cost of carbon emissions, the results show that the three most influential substances are sinter, coke, and pellets. When carbon dioxide emissions are considered, the total cost will increase by 165.3 CNY/t iron, and unit exergoeconomic cost gradually increases with the progress of the production process.